The fellowship of the saints in contemporary South African society - Floor, L. (Koers, 1974)
The subject of this study is: What does the fellowship of the saints that we practise in the Church, mean to us in the present South African society. The division of the subject is as follows: Firstly an analysis of the concept fellowship of the saints; secondly some remarks about the Church in the present situation; and thirdly a closer look at the meaning the fellowship of the saints can have on our behaviour in society.